The Networking Sites in Student Teaching and Learning. A Case Study at Zimbabwean University - Doris Chasokela (Scientia Publica Media, 2024)
The present-day university students, colloquially referred to as ‘millennial learners’ or ‘digital natives’, are a generation of learners that have grown up with the internet. Such students utilize Web 2.0 tools which include SNSs, which are easily accessible on electronic devices that are connected to the internet, presenting a lot of opportunities to enhance student teaching and learning. However, these tools have their downside: hence the need to assess the impact of SNSs on teaching and learning in universities. The study used the interpretive paradigm, qualitative approach method, and a case study design. Purposive sampling was used to select the participants who were composed of departmental chairpersons, lecturers, and students. Data were thereafter collected using interviews and were thematically analyzed. The study also established that participants used SNSs such as Facebook, YouTube, and instant messaging applications like WhatsApp and wikis. The Web 2.0 tools were used for sharing educational materials, research purposes, online tutorials, and study group discussions. The study also revealed the drawbacks and barriers that are associated with the implementation of SNSs in teaching and learning as addiction; negative socialization; cyberbullying health concerns, unreliable information, and reduced academic performance. The study recommends that the use of SNSs by students must be controlled. Students must be educated on the effective use of Web 2.0 tools while lecturers should be trained on how to implement SNSs in pedagogical processes and the use of technological tools.